2006
DOI: 10.1111/j.1365-2753.2006.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Research utilization and clinical nurse educators: a systematic review

Abstract: Few studies have examined clinical nurse educators and the determinants of their research utilization behaviour in clinical practice. Future research on clinical nurse educators needs to focus on the outcomes of research utilization, including the effectiveness of their role as facilitators and the contexts in which they practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
11

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 43 publications
3
56
0
11
Order By: Relevance
“…[14][15][16][17][18] A common challenge that all decision-makers (i.e., clinicians, patients, managers, policy-makers) face relates to the lack of skills in knowledge management and infrastructure (i.e., the sheer volume of research evidence currently produced, access to research evidence, time to read and the skills to appraise, understand and apply research evidence). For example, if a general internist wanted to keep abreast of the primary clinical literature relevant to this field, she would need to read 17 articles daily.…”
Section: What Are Its Determinants?mentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18] A common challenge that all decision-makers (i.e., clinicians, patients, managers, policy-makers) face relates to the lack of skills in knowledge management and infrastructure (i.e., the sheer volume of research evidence currently produced, access to research evidence, time to read and the skills to appraise, understand and apply research evidence). For example, if a general internist wanted to keep abreast of the primary clinical literature relevant to this field, she would need to read 17 articles daily.…”
Section: What Are Its Determinants?mentioning
confidence: 99%
“…20 Lack of skills needed for appraising evidence has been a challenge to all stakeholder groups because, until recently, this skill set has not been a traditional component of most educational curricula. 21,22 For example, Sekimoto and colleagues 23 found that physicians in their study believed a lack of evidence for the effectiveness of a treatment was equivalent to the treatment being ineffective. Similarly, in another study, public health decision-makers identified a lack of skill in critical appraisal of evidence.…”
Section: What Are Its Determinants?mentioning
confidence: 99%
“…A common challenge that all decision makers face relates to the lack of knowledge management skills and infrastructure (the huge volume of research evidence currently produced, access to research evidence, time to read and skills to appraise, understand and apply research evidence) [14,17]. Better knowledge management is necessary, but this is insufficient to ensure effective knowledge translation, given other challenges that may operate at different levels including the health care system (e.g., financial disincentives), health care organization (e.g., lack of equipment or personnel), health care teams (e.g., local standards of care not aligned with recommended practice), individual health care professionals (e.g., knowledge, attitudes, and skills), and patients (e.g., low adherence to recommendations) [18].…”
Section: What Are the Determinants Of Successful Knowledge Translation?mentioning
confidence: 99%
“…Example one Milner et al (2006) report that for their systematic review of the literature regarding clinical nurse educators and research utilization, they used a framework that attempts to describe the complexity of the topic under review. The following quote explains how they used the framework and the reviewers go on to identify how their results did and did not map onto this framework and the utility of this exercise.…”
Section: Conceptual Framework For Beme Systematic Reviewsmentioning
confidence: 99%